Study of life history traits of Culex pipiens Linnaeus, 1758 (Dipter (Diptera: Culicidae) in Labor a: Culicidae) in Laboratory in Erbil pr y in Erbil province-Ir vince-Iraq - Dlpak Birkhader Yaba; Shamall Abdulla Al-Muffti (Polytechnic Journal)
This study aimed to study some biological aspects of different stages of Culex pipiens Linnaeus, 1758 in a laboratory that gathered randomly from four regions in Iraq's Kurdistan from Erbil. The results of the current study revealed that the eggs were laid in rafts, and the egg was elongated in shape, which was narrowed in one end. The mean number of laid eggs was 187.4 eggs; the mean hatching percentage was 83.07%, and the mean incubation period was 28.3 hours. The mean length of the first, second, third, and fourth larval instar was 2.21, 3.27,4.72, and 5.73 mm, respectively. The mean duration was 46.53, 46.41, 46.19, and 46.81 hours, respectively. The overall duration of the larval stage was 185.94 hours; the mean length of pupae was 5.19 mm, while the mean width was 1.81mm, and the mean duration of pupae was 47.50 hours. The adult mosquitoes, the females and males, were distinguished by the antenna. The mean length of an adult female was 5.05mm, and the width was 1.34mm, while in males, the mean length and width were 3.81,0.95 mm, respectively. The mean Preoviposition period was 52.27 hours, the mean oviposition period was 121.07 hours, and the mean post-oviposition period was found to be 26.18 hours; the mean generation of the female adult was 435.38 hours, while the mean generation in male adults was 261.41 hours.